Reimaging Teacher Resilience for Flourishing - Junjun Chen (2024)
Abstract This paper aimed to re-conceptualize teacher resilience, to develop the Teacher. Resilience Inventory, and to explore the impact of teacher resilience on job satisfaction and turnover intention using three sets of teacher samples from China. The validity of the Teacher Resilience Inventory was tested using content validity, construct validity, criterion validity, and cross validity. The results yielded the five dimensions of teacher resilience, namely, physical, emotional, psychological, social, and spiritual resilience, to re-conceptualize teacher resilience. The Teacher Resilience Inventory outlines a general picture of the resilience experience of teachers at work from a multidimensional perspective. Results also showed that teacher resilience significantly related to job satisfaction and turnover intention. This paper will advance the knowledge base on teacher resilience. It will also support teachers to negotiate and navigate demands and resources for desirable outcomes in their everyday life, during constant change and unprecedented uncertainties.